PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP MINAT BELI DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA DEALER HONDA JAYA TERANG 2 SITUBONDO - Umma, Hoyyirotul; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of the study was to determine the effect of service quality and brand image on purchase intention and customer satisfaction as an intervening variable at Honda Jaya Terang 2 Situbondo dealers. The sampling technique used in this study was simple random sampling of 98 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that service quality has a positive and significant effect on consumer satisfaction, brand image has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on purchase intention, brand image has a negative but not significant effect on purchase intention, consumer satisfaction has a positive and significant effect on purchase intention, service quality has a positive but not significant effect on purchase intention through consumer satisfaction, brand image has a positive and significant effect on purchase intention through consumer satisfaction.